2012
DOI: 10.5578/tt.3414
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional observational study on the influence of chronic obstructive pulmonary disease on activities of daily living: the COPD-Life study

Abstract: A cross sectional observational study on the influence of chronic obstructive pulmonary disease on activities of daily living: the COPD-Life study ÖZET Kronik obstrüktif akciğer hastalığının günlük yaşam aktivitelerine etkilerini araştırmaya yönelik kesitsel gözlem çalışması: KOAH'la Yaşam çalışması Giriş: Çalışma kronik obstrüktif akciğer hastalığı (KOAH)'nın hastaların günlük yaşam aktivitelerine etkilerinin ve hastaların günlük yaşamlarını sürdürme biçimleri ve gereksinimlerinin belirlenmesi amacıyla tasarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
1
17
0
4
Order By: Relevance
“…Two other reports corroborated that the more severe the dyspnoea symptom, the lower utility patients place on their health, though the specific levels of breathlessness were described differently (table 3) [43,49]. Other structured surveys, without reporting utility values, also suggested dyspnoea as burdensome and a very important consideration in COPD-related decision-making [31,[50][51][52][53][54][55][56][57][58]. Table 4 summarises the results related to the importance of adverse events.…”
Section: /3 +++− Moderate Certainty Due To Risk Of Bias ¶ ¶mentioning
confidence: 79%
“…Two other reports corroborated that the more severe the dyspnoea symptom, the lower utility patients place on their health, though the specific levels of breathlessness were described differently (table 3) [43,49]. Other structured surveys, without reporting utility values, also suggested dyspnoea as burdensome and a very important consideration in COPD-related decision-making [31,[50][51][52][53][54][55][56][57][58]. Table 4 summarises the results related to the importance of adverse events.…”
Section: /3 +++− Moderate Certainty Due To Risk Of Bias ¶ ¶mentioning
confidence: 79%
“…10 In this respect, a recent study performed in Turkey in 497 stable COPD patients suggested that reducing breathlessness was more of an incentive to seeking treatment than was controlling productive cough. 33 It has been reported in the literature that COPD drives more healthcare consumption than many other chronic diseases. For example, in the United Kingdom, it was reported that the number of physician consultations for respiratory diseases is over three times as high as that for diseases of the circulatory or digestive system.…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish, national, observational study of 497 COPD patients found that two-thirds of patients knew their diagnosis, 80% knew they required lifelong treatment, 80% experienced respiratory symptoms, and 90% reduced their daily activities due to dyspnea. 39 A study by Miravitlles and others found that only 27% of patients with airflow limitation identified by spirometry had previously been diagnosed with COPD. 40 Those with a diagnosis of COPD had more severe disease and greater impairment in HRQL and activities of daily living (ADL).…”
Section: Discussionmentioning
confidence: 99%